Buku Jihad Terjemahan dari Bahasa Arab dan Potensi Radikalisme Beragama di Lembaga Pendidikan - Munip, Abdul (IAIN Ponorogo, 2017)
This paper describes how the jihad books translated from Arabic potentially strengthen radicalism in Indonesia. In fact, the jihad books are written and translated by the jihadists themselves as their reference for acting global jihad. These books are disseminated by their publisher or posted in their website. Most of these jihadists website provide information, articles and eBooks that can be downloaded for free. Most of these books discuss about the meaning, law, financing, strategy and targets of jihad. There are a number of concepts that potentially affect the readers toward an attitude of radicalism. These concepts are jihad is war, suicide bombing is part of jihad, and the thoghut government is a target of their jihad. These translated books also potentially affect the growth of a radical and intolerant attitude in educational institutions, because it can creep through the mentoring activities of the Islamic religion in College, Rohani Islam (Rohis) in SMA/SMK, friendship networks and hidden agendas of the institutions manager who opposed the ideology of the State. Therefore, to minimize the negative impact of the these translated books, the concept of soft jihad is need to be introduced and promoted.ØªØ¨ÙÙ ÙØ°Ù Ø§ÙÙ ÙØ§ÙØ© Ø¹Ù Ø¥ØØªÙ Ø§Ù ÙØªØ¨ Ø§ÙØ¬ÙØ§Ø¯ Ø§ÙÙ ØªØ±Ø¬Ù Ø© Ù Ù Ø§ÙØ¹Ø±Ø¨ÙØ© ÙÙ ØªØ¹Ø²ÙØ² Ø§ÙØªØ·Ø±Ù Ø§ÙØ¯ÙÙÙ ÙÙ Ø¥ÙØ¯ÙÙÙØ³ÙØ§. ÙÙÙ Ø§ÙÙØ§ÙØ¹Ø Ø£ÙÙ Ø§ÙÙØ§ØªØ¨ÙÙ ÙØ§ÙÙ ØªØ±Ø¬Ù ÙÙ ÙÙØ°Ù Ø§ÙÙØªØ¨ ÙÙ Ø§ÙØ¬ÙØ§Ø¯ÙÙÙ Ø£ÙÙØ³ÙÙ ÙÙØ¬Ø¹ÙÙÙÙØ§ Ù ØµØ§Ø¯Ø± ÙÙ Ø¹Ù ÙÙØªÙÙ Ø§ÙØ¬ÙØ§Ø¯ÙØ© Ø§ÙØ¹Ø§ÙÙ ÙØ©. ÙØªÙØ´Ø±ÙØ°Ù Ø§ÙÙØªØ¨ Ù Ø·Ø¨Ø¹Ø© Ø§Ù Ù ÙØ´ÙØ±Ø© ÙÙ Ù ÙØ§ÙØ¹ÙÙ Ø¹ÙÙ Ø§ÙØ¥ÙØªØ±ÙØª. ÙØªÙÙØ± Ù Ø¹Ø¸Ù ÙØ°Ù Ø§ÙÙ ÙØ§ÙØ¹ Ø§ÙÙ Ø¹ÙÙÙ Ø§Øª ÙØ§ÙÙ ÙØ§ÙØ§Øª ÙØ§ÙÙØªØ¨ Ø§ÙØ¥ÙÙØªØ±ÙÙÙØ© Ø§ÙØªÙ ÙÙ ÙÙ ØªØÙ ÙÙÙØ§ Ù Ø¬Ø§ÙØ§Ù. ÙÙØ«ÙØ± Ù Ù ÙØ°Ù Ø§ÙÙØªØ¨ ÙØªØØ¯Ø« ØÙÙ Ù Ø¹ÙÙ Ø§ÙØ¬ÙØ§Ø¯Ø ÙØÙÙ ÙØ ÙØªÙ ÙÙÙÙØ ÙØ§Ø³ØªØ±Ø§ØªÙØ¬ÙØªÙØ ÙÙ Ù ÙØ¬Ø¨ Ø¹ÙÙÙÙ Ø§ÙÙØªÙ. ÙÙÙØ§ ÙØ¹Ø¯Ø¯ Ù ÙØ§ ÙÙ ÙØ§ÙÙÙ Ø§ÙØ¬ÙØ§Ø¯ÙØ© Ø§ÙØªÙ ÙØØªÙ Ù Ø£Ù ØªØ¤Ø«Ø±Ø¹ÙÙ Ø§ÙÙØ±ÙØ§Ø¡ Ø¥ÙÙ Ø§ÙØªØ·Ø±Ù Ø§ÙØ¯ÙÙÙ. ÙÙ Ù ÙØ°Ù Ø§ÙÙ ÙØ§ÙÙÙ Ø£Ù Ø§ÙØ¬ÙØ§Ø¯ ÙÙ Ø§ÙØØ±Ø¨ Ø§Ù Ø§ÙÙØªÙ ÙØ§ ØºÙØ±Ø ÙØ£Ù Ø§ÙØªÙØ¬ÙØ±Ø§ÙØ§ÙØªØØ§Ø±Ù ÙÙØ¬Ø²Ø¡ Ù Ù Ø§ÙØ¬ÙØ§Ø¯ ÙÙØ³Ù ÙÙÙ Ø¨Ø¹Ù ÙÙØ© Ø¥Ø³ØªØ´ÙØ§Ø¯ÙØ©Ø ÙØ§Ù Ø§ÙØÙÙÙ Ø© Ø§ÙØ·Ø§ØºÙØªÙØ© ÙÙ Ø§ÙØªÙ ÙØ¬Ø¨ Ø¹ÙÙÙØ§ Ø§ÙØØ±Ø¨ Ø£Ù Ø§ÙÙØªÙ. ÙØªØØªÙ Ù ÙØ°Ù Ø§ÙÙØªØ¨ Ø§ÙÙ ØªØ±Ø¬Ù Ø© Ø§ÙØ¬ÙØ§Ø¯ÙØ© Ø£Ù ØªØ¤Ø«Ø± Ø¹ÙÙ ÙÙ Ù Ø§ÙÙ ÙØ§ÙÙ Ø§ÙÙ ØªØ·Ø±ÙØ© ÙØ§ÙÙ ØªØ¹ØµØ¨Ø© ÙÙ Ø§ÙÙ Ø¤Ø³Ø³Ø§Øª Ø§ÙØªØ¹ÙÙÙ ÙØ©Ø ÙØ°ÙÙ Ù Ù Ø®ÙØ§Ù Ø£ÙØ´Ø·Ø© Ø§ÙØ¥Ø±Ø´Ø§Ø¯ Ø¥ÙÙ Ø§ÙØ¯ÙÙ Ø§ÙØ¥Ø³ÙØ§Ù Ù (mentoring Agama Islam) ÙÙ Ø§ÙØ«Ø± Ø§ÙØ¬Ø§Ù Ø¹Ø§ØªØ ÙÙ Ù Ø®ÙØ§Ù Ø£ÙØ´Ø·Ø© Ø§ÙÙ ÙØ¸Ù Ø© Ø§ÙØ·ÙØ§Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© (Rohis) ÙÙ SMA/SMKØ ÙÙ Ù Ø®ÙØ§Ù Ø§ÙØµØ¯Ø§ÙØ© Ø§ÙØ´Ø¨ÙØ© Ø¨ÙÙ Ø§ÙØ·ÙØ§Ø¨Ø Â ÙÙØ°ÙÙ Ù Ù Ø®ÙØ§Ù Ø§ÙØ¨Ø±Ø§Ù Ø¬ Ø§ÙØ®ÙÙØ© ÙØ¯Ù Ø§ÙÙ Ø¤Ø³Ø³Ø§Øª Ø§ÙØªØ¹ÙÙÙ ÙØ© Ø§ÙØªÙ ØªØ¹Ø§Ø±Ø¶ Ø£ÙØ¯ÙÙÙÙØ¬ÙØ© Ø§ÙØÙÙÙ Ø© Ø§ÙØ¥ÙØ¯ÙÙØ³ÙØ©. ÙÙØ°ÙÙØ ÙÙØ¨ØºÙ Ø£Ù ÙÙØ¯Ù Ù ÙÙÙÙ Ø§ÙØ¬ÙØ§Ø¯ Ø§ÙÙÙÙØ© ÙØ¯Ù Ø§ÙÙ Ø³ÙÙ ÙÙ Ø§ÙØ¥ÙØ¯ÙÙØ³ÙÙÙ ÙÙÙØµØ§Ù Ø§ÙØ£Ø«Ø±Ø§ÙØ³ÙØ¨Ù ÙÙØ°Ù Ø§ÙÙØªØ¨ Ø§ÙÙ ØªØ±Ø¬Ù Ø©.